Unusual Metastatic Site - Peritoneal Metastasis in Malignant Melanoma: Case Report - Anjos, Amanda da Silva (2021)
Introduction: Cutaneous melanoma is a tumor with great capacity for metastasis. One of the possible but quite rare scenarios is when the metastasis is lodged in the peritoneum (peritoneal carcinomatosis). Case report: 61-year-old female patient, referred by a suspected left inguinal mass and 2 cm hyperchromic lesion, with regression area in the left lower limb. The patient underwent left inguinal lymphadenectomy and resection of the skin lesion, which revealed invasive extensive superficial cutaneous malignant melanoma, Breslow depth 1.2 mm and Clark II level, as well as lymph node metastasis. Adjuvant treatment included radiotherapy and chemotherapy. During follow-up, 8 months later, abdominal ultrasound and computed tomography showed hypoechoic, heterogeneous, and beveled solid nodular image, poorly defined and delimited in left para-aortic projection, with 12.7x6.7x4.8 cm. In exploratory laparotomy, a large retroperitoneal mass was found on the left flank, involving the Treitz angle, and revealed the presence of peritoneal carcinomatosis. The anatomopathological report showed a poorly differentiated malignant infiltrative epithelioid neoplasm, compatible with the clinical history of melanoma. The patient died after consultation with clinical oncology. Conclusion: There are few cases of peritoneal metastasis of melanoma reported in the literature. However, its possibility of occurrence and the therapeutic options available must be taken into account, in addition to understanding its impact on the patient’s prognosis. Although rare, peritoneal carcinomatosis should be considered when patients with a personal history of melanoma have non-specific abdominal complaints, such as the patient in the case reported.